Small electronic load. Design and analysis of a small electronic load for testing on-board DC/DC converters - Rosén, Lukas; Samimi, Sahar (My University, 2012)
Electronic loads are used at Ericsson AB for test and verification of on-board DC/DC converters. The problem with the existing electronic loads is that they require cables to connect to the board due to their dimensions. Cables will introduce inductance in the load current path and affect the testing results, especially the current slew rate. In this thesis a new load design is developed which can be soldered directly on the circuit board and eliminating the use of cables. In this way the converters can be tested with higher current slew rates than before, meeting future needs. With the existing electronic loads the maximum achievable current slew rate was 2.5 A/s from a 3.3 V supply using 80 cm cable. The prototype designed in this thesis managed to achieve 32 A/s for the same supply voltage.
Keywords: Elkraftteknik; Electric power engineering